The role of language in recognition and categorization of emotional states. Relation between “me” and emotion in cultural context - GASIUL, HENRYK (Studia Psychologica: Theoria et praxis, 2015)
The article concerns the analysis of the importance of language in the self-determination of one’s emotional states and his/her determination of the same in another person. In the first part of the article the author presents the difficulties with the categorization of emotions which are the result of using different languages. Further, he proves, that the broadly understood culture, in which a language is an indispensable dimension, is of the key significance in the comprehension of emotions. Taking into consideration the fact that the emotions are connected to the “subjective self” in a special way, the fundamental role should be attributed to the shaping of the mental structure which defines the character of this “subjective self”. The collectivist and individualist cultures are the examples the dissimilarities in the self-structure shaping. They delineate the ways in which emotional states are experienced, and what types of the experienced emotions dominate. The language as a fundamental system of social communication confers the meanings on emotional states. Through this meaning it explains the variability of experiencing the emotions and guides the ways the emotional states are categorized.